2013
DOI: 10.1002/jeab.56
|View full text |Cite
|
Sign up to set email alerts
|

Discounting of delayed and probabilistic losses over a wide range of amounts

Abstract: The present study examined delay and probability discounting of hypothetical monetary losses over a wide range of amounts (from $20 to $500,000) in order to determine how amount affects the parameters of the hyperboloid discounting function. In separate conditions, college students chose between immediate payments and larger, delayed payments and between certain payments and larger, probabilistic payments. The hyperboloid function accurately described both types of discounting, and amount of loss had little or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
47
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 33 publications
11
47
4
Order By: Relevance
“…In contrast to previous research (e.g., Green et al, 2014), for delayed losses we found a significantly greater k as magnitude increased ( p = 0.001, t 62 = 3.35). However, consistent with previous research (Green et al, 2014), we did not observe a magnitude effect between probabilistic losses of $1000 and $10 ( p = 0.12, t 69 = 1.56).…”
Section: Methodscontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to previous research (e.g., Green et al, 2014), for delayed losses we found a significantly greater k as magnitude increased ( p = 0.001, t 62 = 3.35). However, consistent with previous research (Green et al, 2014), we did not observe a magnitude effect between probabilistic losses of $1000 and $10 ( p = 0.12, t 69 = 1.56).…”
Section: Methodscontrasting
confidence: 99%
“…In contrast to previous research (e.g., Green et al, 2014), for delayed losses we found a significantly greater k as magnitude increased ( p = 0.001, t 62 = 3.35). However, consistent with previous research (Green et al, 2014), we did not observe a magnitude effect between probabilistic losses of $1000 and $10 ( p = 0.12, t 69 = 1.56). Finally, and also consistent with previous research (e.g., Estle et al, 2006), we observed significantly greater h s for gains of $1000 compared to $10 ( p < 0.001, t 38 = 3.76).…”
Section: Methodscontrasting
confidence: 99%
See 3 more Smart Citations